Disability in the Family: John and Alice Dewey Raising Their Son, Sabino. Issue 2 (February 2018) - Danforth, Scot
Background/Context: The current biographic understanding of John Dewey's experience adopting and raising an Italian boy named Sabino emphasizes the theme of finding an emotional replacement for Morris and Gordon, two young sons who had tragically died on family trips to Europe. Lacking is substantive attention to the fact that John Dewey's son had a physical disability who grew up during the early surge of eugenics thought in American popular life. The leading biographer Jay Martin has portrayed John and Alice Dewey as rescuing Sabino from poverty, an experience that gave John Dewey "a special empathy for the second-best, the second-class citizen, the loser in society. " What is missing from all biographic research on the Deweys is their experience of raising a boy with a physical disability during a historical time when disabilities were highly stigmatized. Purpose/Objective/Research: The purpose of this historical study is to supplement the current understanding of John Dewey fathering an adopted son with an account that attends to the fact that young Sabino had a physical disability. Working in the disability studies tradition, this analysis explores both how the Deweys contended with Sabino's bone tuberculosis as an illness requiring medical treatment and how they navigated the complex political context of deeply discriminatory attitudes surrounding disabled persons. The conclusion initiates a discussion of the larger questions concerning how the experiences of fathering a boy impacted directly by disability oppression might have influenced John Dewey's political activity and scholarship. Research Design: This historical analysis utilizes prior biographic research, published and unpublished works by John Dewey, and primary historical documents such as family letters and medical and popular publications of the era. Conclusions/Recommendations: This analysis finds that John and Alice Dewey were very loving and attentive parents who endured many struggles due to their child's disability. They worried about their son's health, and they capably navigated the available medical options. They were troubled by their son's suffering and pain, and they worked together with great consistency to comfort and support him. Further, they directly confronted disability prejudice, including educational segregation, and worked assiduously against the powerful cultural assumption that their disabled son should lead a life of anything less than full participation in the community. The article concludes with a preliminary examination of how these experiences influenced John Dewey's political writings and activities.